High Color Purity Lead‐Free Perovskite Light‐Emitting Diodes via Sn Stabilization. Issue 8 (1st March 2020) - Liang, Hongyan; Yuan, Fanglong; Johnston, Andrew; Gao, Congcong; Choubisa, Hitarth; Gao, Yuan; Wang, Ya‐Kun; Sagar, Laxmi Kishore; Sun, Bin; Li, Peicheng; Bappi, Golam; Chen, Bin; et al.
Abstract: Perovskite‐based light‐emitting diodes (PeLEDs) are now approaching the upper limits of external quantum efficiency (EQE); however, their application is currently limited by reliance on lead and by inadequate color purity. The Rec. 2020 requires Commission Internationale de l'Eclairage coordinates of (0.708, 0.292) for red emitters, but present‐day perovskite devices only achieve (0.71, 0.28). Here, lead‐free PeLEDs are reported with color coordinates of (0.706, 0.294)—the highest purity reported among red PeLEDs. The variation of the emission spectrum is also evaluated as a function of temperature and applied potential, finding that emission redshifts by <3 nm under low temperature and by <0.3 nm V −1 with operating voltage. The prominent oxidation pathway of Sn is identified and this is suppressed with the aid of H3 PO2 . This strategy prevents the oxidation of the constituent precursors, through both its moderate reducing properties and through its forming complexes with the perovskite that increase the energetic barrier toward Sn oxidation. The H3 PO2 additionally seeds crystal growth during film formation, improving film quality. PeLEDs are reported with an EQE of 0.3% and a brightness of 70 cd m −2 ; this is the record among reported red‐emitting, lead‐free PeLEDs. Abstract : Sn‐based perovskite light‐emitting diodes with ultra‐high red color purity, a brightness of 70 cd m −2, and 24 nm linewidth are prepared. The devices show excellent color stability under different temperatures, power, and operating voltage. Based on the oxidation pathway of Sn, H3 PO2 is chosen to suppress the oxidation of Sn 2+ and slow down the crystal growth, simultaneously.